Addition of bortezomib to standard dose chop chemotherapy improves response and survival in relapsed mantle cell lymphoma. (22nd August 2014) - Furtado, Michelle; Johnson, Rod; Kruger, Anton; Turner, Deborah; Rule, Simon
Summary The proteasome inhibitor, bortezomib, potentially increases cell sensitivity to chemotherapy. This study was performed to determine the overall response rate (ORR), overall survival (OS), progression‐free survival (PFS) and toxicity of CHOP (cyclophosphamide, doxorubicin, vincristine and prednisolone) compared to CHOP + bortezomib chemotherapy in mantle cell lymphoma (MCL) patients at first relapse. Forty‐six patients were randomly assigned to standard dose CHOP ± bortezomib 1·6 mg/m2 given on a 21‐d cycle for up to eight cycles of treatment. Median age was 71 years (CHOP arm) and 69 years (CHOP‐bortezomib arm). Median Eastern Cooperative Oncology Group performance status was 1 (CHOP) and 0 (CHOP‐bortezomib) with 65% and 52%, respectively, having a disease stage of IV. ORR was 47·8% (CHOP) and 82·6% (CHOP‐bortezomib). Complete response rate was 21·7% (CHOP) vs. 34·8% (CHOP‐bortezomib); partial response rate was 26·1% (CHOP) vs. 47·8% (CHOP‐bortezomib). Median OS was 11·8 months (CHOP) and 35·6 months (CHOP‐bortezomib) (P = 0·01, Hazard ratio [HR] 0·37 [95% confidence interval (CI) 0·16–0·83)] and there was a non‐significant improvement in PFS: 8·1 months (CHOP) and 16·5 months (CHOP‐bortezomib) [P = 0·12, HR 0·60 (95% CI 0·31–1·15)]. Severe (≥grade 3) sensory neuropathy was similar in both arms (4·3% CHOP vs. 6·5% CHOP‐bortezomib). We conclude that the addition of bortezomib to CHOP chemotherapy for relapsed MCL significantly improves outcome with a manageable increase in toxicity.